Palbociclib Induces the Apoptosis of Lung Squamous Cell Carcinoma Cells via RB-Independent STAT3 Phosphorylation - Wenjing Xiang; Wanchen Qi; Huayu Li; Jia Sun; Chao Dong; Haojie Ou; Bing Liu (Current Oncology, 2022)
Lung squamous cell carcinoma (LUSC) treatment response is poor and treatment alternatives are limited. Palbociclib, a cyclin-dependent kinase (CDK) 4/6 inhibitor, has recently been approved for hormone receptor-positive breast cancer patients and applied in multiple preclinical models, but its use for LUSC therapy remains elusive. Here, we investigated whether palbociclib induced cell apoptosis and dissected the underlying mechanism in LUSC. We found that palbociclib induced LUSC cell apoptosis through inhibition of Src tyrosine kinase/signal transducers and activators of transcription 3 (STAT3). Interestingly, palbociclib reduced STAT3 signaling in LUSC cells interfered by retinoblastoma tumor-suppressor gene (RB), suggesting that pro-apoptosis effect of palbociclib was independent of classic CDK4/6-RB signaling. Furthermore, palbociclib could suppress IL-1β and IL-6 expression, and therefore blocked Src/STAT3 signaling, which were rescued by either recombinant human IL-1β or IL-6. Moreover, Myc mediated the sensitivity of LUSC cells to palbociclib. Our discoveries demonstrated that palbociclib induces apoptosis of LUSC cells through the Src/STAT3 axis in an RB-independent manner, and provided a reliable experimental basis of clinical studies in LUSC patients.